Population‐level impact of initiating pharmacotherapy and linking to care people with opioid use disorder at inpatient medically managed withdrawal programs: an effectiveness and cost‐effectiveness analysis. - Savinkina, Alexandra; Madushani, Rajapaksha W.M.A.; Eftekhari Yazdi, Golnaz; Wang, Jianing; Barocas, Joshua A.; Morgan, Jake R.; Assoumou, Sabrina A.; Walley, Alexander Y.; Linas, Benjamin P.; Murphy, Sean M. (Addiction, 2022)
Background and Aims: Medications for opioid use disorder (MOUD) are shown to reduce opioid use and the risk of overdose. People with opioid use disorder (OUD) who exit inpatient medically managed withdrawal programs (detox) without initiating MOUD and linking to outpatient care have high rates of overdose. While detox encounters provide a theoretical opportunity for MOUD initiation, this is not ubiquitous in the United States. We used simulation modeling to estimate the population‐level health effects and cost‐effectiveness of a policy encouraging MOUD initiation during inpatient detox encounters. Design, Setting and Participants: We employed a dynamic population state‐transition model to evaluate the effectiveness and cost‐effectiveness of using detox programs as venues for initiating MOUD in Massachusetts, United States. We compared standard of care, where no detox patients initiate MOUD or link to outpatient MOUD providers, to strategies of offering MOUD to detox patients and linking those patients to outpatient MOUD. Measures: Budgetary impact to the Massachusetts health‐care sector, incremental cost‐effectiveness ratios (ICER) and total counts and percentage differences of fatal overdoses prevented. Findings: Initiating MOUD in detox with perfect linkage to outpatient MOUD would reduce fatal overdoses by 4.5% [95% confidence interval (CI) = 2.3–5.9], at an ICER of $56 000 per quality‐adjusted life‐year (QALY) gained, compared with the standard of care. With moderate linkage, fatal overdoses would be reduced by 2.3% (95% CI= 1.2–3.1) with an ICER of $78 500 per QALY gained, compared with standard of care. Budgetary increase to Massachusetts health‐care spending ranged from 0.5–1%. Conclusion: A simulation model indicates that initiation of medications for opioid use disorder and linkage policies among detox patients in Massachusetts, USA could prevent fatal opioid overdoses in the opioid use disorder population and would be cost‐effective from a health‐care sector perspective.